River Basin Pollution, Pollution Causes, Consequences and their Prevention - Nurbek, Toshturdiyev (ANTIS PUBLISHER, 2024)
This scientific article provides extensive information about river and river basin pollution. For many years, the rivers, which are considered as sources of fresh water, have been polluted. This, in turn, has become one of the biggest global problems. Information about the causes and consequences of pollution was also given.